Efektivitas penggunaan media "VIRDAN" dalam meningkatkan pengetahuan dan keterampilan mahasiswa pada Mata Kuliah Asuhan Kebidanan Neo, Bayi Dan Balita - Kirana Dewi Pertiwi; Yuliasti Eka Purnamaningrum; Dwika Suryaningdyah; Uki Wulanggita (Health Educational Laboratory, 2024)
Background: The importance of graduates' competence in providing immunizations to babies, the problem of unavailability of vaccines in the laboratory, and the task of educational staff in supporting smooth practice in the laboratory, the author took the initiative to create a Mock Basic Routine Immunization Vaccine (VIRDAN) media to become an effective learning medium in the Neonate, Infant, and Toddler Midwifery Care course in 2019. This VIRDAN media has been produced in limited quantities but has never been tested for learning neonate, infant, and toddler obstetric care courses. Purpose: Knowing the effectiveness of VIRDAN media in increasing student knowledge. Method: This study is an experimental study with a randomized pre post test with control group design conducted with direct observation on students. Results: There was a significant difference in student practicum test scores in the experimental group and control class. Obtained t table from db 44 at a significance level of 5% (0.05) is 1.680. So the value of t counts > t of the table (11.405 > 1.680) and the significance value is less than 0.05 (p = 0.000 < 0.05). Conclusion: VIRDAN as a medium capable of improving the skills of students better, the value of the experimental group is significantly better.